The Effect of Concentrate/Iron Ore Ratio Change on Agglomerate Phase Composition - Mária Fröhlichová; Dušan Ivanišin; Róbert Findorák; Martina Džupková; Jaroslav Legemza (Metals, 2018)
The work is focused on studying the influence of the ratio of concentrate to iron ore on the phase composition of the iron ore agglomerate. The concentrate has significantly higher iron content than used iron ore, and is a determining factor, which influences the richness of the batch and consequently, the richness of the agglomerate. The increased iron content in the agglomerate can be achieved by adjusting the raw material ratio in which iron ore materials are added to the agglomeration mixture. If the ratio is in favor of iron ore this reflects in lower iron content in the resulting agglomeration mixture. If the ratio is in favor of a concentrate, which is finer, the fraction share of less than 0.5 mm will be increased, the permeability of the batch will be reduced, the performance of the sintering belt will decrease and the presence of solid pollutants will increase. The possibility of concentrate replacement by iron-rich iron ore with granulometry similar to that of concentrate was experimentally verified. The effect of the concentrate replacement by the finer iron-rich ore was tested in a laboratory sintering pan. There were performed six sinterings, with gradually changing ratio concentrate/iron ore (C/O). The change in the ratio of concentrate to iron ore, does not cause the occurrence of new phases, only the change in their prevalence, which does not bring a significant change of the qualitative indicators of the compared agglomerates. Concentrate replacement by iron ore up to 50% was optimal from technological, quality, and environmental aspects.